Fuel Treatment Longevity in Ponderosa Pine-Dominated Forest 24 Years After Cutting and Prescribed Burning - Hood, Sharon M.; Keyes, Christopher R.; Bowen, Katelynn J.; Lutes, Duncan C.; Seielstad, Carl (Frontiers in Forests and Global Change, 2020)
Fuels reduction treatments to mitigate fire behavior are common in ponderosa pine ecosystems of the western United States. While initial impacts of fuel treatments have been reported, less is known about treatment longevity as live and dead fuels change with time. We analyzed fuel dynamics in ponderosa pine–Douglas-fir forests 21-23 years following experimental fuel reduction designed as two independent studies of cutting combined with burning: one tested a commercial thinning strategy, while a second tested a retention shelterwood strategy to reduce fuels while also restoring ponderosa pine forests. Treated units were harvested in 1992 and half of the units were prescribed burned one-to-two years later. After 22 to 23 years post-treatment, few differences in fuel load persist and all treatments have increased ladder fuels in the form of live saplings and seedlings. Canopy fuel loads were lower in treated units compared to untreated control units; however, no other canopy fuel metric differed between treatments. The only persistent difference in surface fuels was in the retention shelterwood, where 1-hour fuels were lower in the treated units compared to control units. Crown fire hazard varied greatly, but means were similar between treatments. The increased hazard was driven by increases in live surface fuels from seedlings and saplings in the retention shelterwood, which increased canopy bulk density and reduced canopy base height. The overstory was still dominated by ponderosa pine 21-23 years later for all treatments, but the smaller size classes were primarily Douglas-fir, suggesting that without future disturbance, dominance will shift from pine to Douglas-fir dominated forests. The exception to this was the cut+fall burn treatment in the commercial thinning, where ponderosa pine outnumbered Douglas-fir trees across all size classes. The treatments that included a broadcast prescribed burn killed many existing seedlings and saplings. Our findings support other studies showing fuel reduction and restoration treatments are most successful with a combination of cutting and burning strategies, but also show that fuel treatments in low-elevation dry forests will likely not remain effective for much longer than historical mean fire return intervals.